Analisis Proses Berpikir Mahasiswa dalam Menyelesaikan Permasalahan Bangun Ruang - Florida Moza (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
Mathematics is the science that teaches numbers and others which are also related to the process of solving a problem. Solving a problem requires a person's thinking process to solve the problem. The thinking process is a step or a path taken to solve a problem. The purpose of this research it’s to explain the thinking process of students in solving problems of geometry. This type of research is a qualitative descriptive study. The subjects in this study were 6 undergraduate students of Mathematics Education at Sanata Dharma University. The research instrument used was a question containing the problem of building space that asked students to think of ways or strategies to put books into a box that has a size and how many books can fit into the box. Furthermore, the interview was conducted to find out the answers that were not understood that came from the student's answers. Data collection techniques in this study were tests and interviews. The data analysis techniques in this study were (1) data reduction; (2) exposure data (display data); (3) drawing conclusions and verification (conclusion drawing / verifying). The results obtained in this study were 1) students could not understand the questions from the questions, 2) Students could provide strategies to solve the problems, and 3). Students still make mistakes in determining the length and width of a block